DEVELOPMENT MODEL OF LEARNING BASKETBALL BASED MODIFICATION GAMES FOR SECONDARY HIGH SCHOOL - Ahmad Hamidi (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this research and development is to produce a model of learning basketball skills on learning physical education for students middle school first. In addition, this research and development is conducted to obtain information in depth about: development and application of learning model of bolabasket skill (hamidi) on basketball game for students of middle school first and know the effectiveness, efficiency and attractiveness of student to model made. This research and development use research & development (R & D) research method from borg and gall. The subjects in this research and development are the students of the first class VII students aged 13-14 years as many as 98 people. The instruments used in this research and development are questionnaires, questionnaires, battery test tests used to collect basic engineering skill data, as well as